Framing resilience for river geomorphology: Reinventing the wheel?. (20th January 2019) - Fuller, Ian C.; Gilvear, Dave J.; Thoms, Martin C.; Death, Russell G.
Abstract: Resilience is a well‐used term in many disciplines, but inconsistently or little applied in river geomorphology and river science. Recent developments in ecosystem ecology conceptualize resilience as comprising system resistance to, and recovery from disturbance. The objectives of this paper are to consider how the concept of resilience in this bivariate form applies to river geomorphology and provide a framework for bridging the disciplines of ecology and geomorphology within the setting of river management, using principles of resilience. River geomorphology sets the physical template upon which lotic processes act, thus, understanding the resilience of this template is critical. The importance of consistency in defining the principles of resilience thinking within the context of river science and management is important especially when promoting ecosystem resilience as a river management goal. The application of resilience thinking with respect to river habitat is provided through a series of examples from Australian and New Zealand river systems. Aim: How is the concept of resilience applied to river geomorphology, and what does a geomorphologically resilient river look like?